Household Dietary Patterns in Food Insecurity Areas - Wijaya, Oki; Widodo, Widodo; Lathifah, Riskhi; Rahmawati, Nur; Rubiyanto, Cahyo Wisnu (AGRARIS: Journal of Agribusiness and Rural Development Research, 2020)
Dietary contributes to sustainable food security. Accordingly, attempts to elevate dietary patterns should be simultaneous and comprehensive, especially to the farmer community living in rural areas, who have two roles, i.e., producers and consumers. In response to that situation, this research aims to analyze household dietary patterns and contributing factors. This research was conducted in Wukirsari Imogiri Bantul. The data used in this research were primary data collected from 63 respondents selected using the cluster sampling approach. Dietary patterns were analyzed using 2Ã—24-hour dietary recall data with a household measure unit and a Desirable Dietary Pattern (DDP). Meanwhile, the contributing factors were analyzed using the Double Linear Regression Approach. Findings indicate that the Desirable Dietary Pattern in Wukirsari was monotonous, confirmed by the resulted DDP score of 60.62. Moreover, the significant factor with a partial impact on household dietary patterns was educational levels. Meanwhile, other factors, e.g., the number of family members, the age of the head of the family, income per capita, rice prices, beneficiaries, and the main job of the head of the family had a simultaneous significant impact, which was also partially insignificant, on dietary patterns.